Characterization of Waste into Liquid Smoke from Wood Powder and Coconut Shell (Cocos nucifera) - Dewi Ermaya (Universitas Serambi Mekkah, 2020)
Liquid smoke is the result of condensation or condensation from the steam resulting from pyrolysis (combustion). From ingredients that contain lotsof lignin, cellulose, hemicellulose and carbon compounds which can be used as preservatives. Sawdust and coconut shell are sawdust, which is waste from the remains of refining wood on furniture and market waste from coconuts which are taken from coconut milk and oil. Both contain cellulose, hemicellulose, and lignin, these ingredients can be made into liquid smoke. The purpose of this study was to utilize sawdust and shell waste as liquid smoke which could be applied to the pickling and clumping industry. Making liquid smoke is done using a pyrolysis device. The liquid smoke formed is filtered. Then the yield was calculated and analyzed the quality of the liquid smoke, namely specific gravity, pH, and color. The results showed that the yield of sawdust was higher than coconut shell, namely 45.09%. And the resulting color is better sawdust.